Quantification of hemoglobin Constant Spring in heterozygote and homozygote by a capillary electrophoresis method - Pornprasert,S. (Wiley-Blackwell, 2015)
Introduction: Capillary electrophoresis (CE) is a high-resolution method for detection of hemoglobin Constant Spring (Hb CS). Methods: The levels of Hb CS quantified by CE were compared among three groups of samples including heterozygote and homozygote of Hb CS as well as Hb H-CS disease classified by DNA molecular diagnosis. The mean corpuscular volume (MCV) of red blood cells was also analyzed among these three groups. Results: Mean±SD of Hb CS level of the homozygote was not significantly different from that of the Hb H-CS disease (1.9±1.8 vs. 2.8±1.3, P=0.13), but it was significantly higher than that of the heterozygote (1.9±1.8 vs. 0.4±0.2, P=0.007). The MCV <70fL was found in Hb H-CS disease only. Conclusion: CE is the preferable method for screening of heterozygote and homozygote of Hb CS. Moreover, in conjunction with a lower MCV (<70fL), this approach provided a high resolution to identify Hb H-CS disease. © 2011 Blackwell Publishing Ltd.